Slope Reinforcement Model Scale Test With X-Block - Karapa, Enos; Harianto, Tri; Muhiddin, A. B.; Irmawaty, Rita (Salehan Institute of Higher Education, 2022)
This study aims to determine the material composition and dimensions of X-block, develop a slope reinforcement model using X-block, evaluate the mechanical behavior of slopes that are reinforced with rock-bound by X-block, and analyze the performance of slope reinforcement using X-block. This research was conducted at Hasanuddin University's soil mechanics and civil engineering structure laboratory. The model scale test was employed in this study. The geometrical speciation of the test box is 150 cm in length, 60 cm in width, and 100 cm in height. The X-block model was produced using concrete with a FC of 25 MPa. The X-block was divided into two types: X-block type 1 and X-block type 2. Tensile strength testing is performed on the X-block. The slopes are made of clay soil and have a slope angle of 70 degrees. The loading test was conducted in three stages: without block, with X-block type 1, and with X-block type 2. The loading test uses a hydraulic pump equipped with a load cell and LVDT. The tensile strength of X-block type 1 is 2.56 MPa, whereas X-block type 2 has a tensile strength of 4.35 MPa. The development of the type X-block design, which is used as a retaining wall material, has shown that it can effectively withstand landslides on the slopes under consideration. The slope safety factor rose dramatically after being reinforced with type X-blocks, reaching 2.73 for both X-block type 1 and X-block type 2.Â Doi: 10.28991/CEJ-2022-08-03-014 Full Text: PDF